The relationship of maternal age, BMI, serum Tenascin-C, and HOMA-IR values with gestational diabetes mellitus - Nazia Feroz; Fauzia Imtiaz; Sonia Siddiqui; Lubna Ali (Journal of the Pakistan Medical Association, 2024)
Objective: To explore the relationship, if any, of gestational diabetes mellitus with maternal age, body mass index, serum tenascin-C and homeostatic model assessment for insulin resistance, and to see if these could act as predictive markers for gestational diabetes mellitus. Method: The case-control study was conducted from February to August 2022 at the outpatient department of gynaecology and obstetrics at the Civil Hospital, Karachi, and comprised pregnant females aged 18-40 years having gestational age 20-34 weeks. After noting down baseline characteristics and anthropometric measurements, the participants were subjected to oral glucose tolerance test on the basis of which they were divided into three groups; pregnant healthy controls in group 1, those with gestational diabetes mellitus on diet control in group 2, and those with gestational diabetes mellitus taking medicines for the condition in group 3. Fasting serum samples were used for further analysis using enzyme-linked immunosorbent assay kits. Data was analysed using SPSS 21. Results: Of the 90 subjects, 30(33.3%) were in group 1 with mean age 26.0±4.9 years, 30(33.3%) were in group 2 with mean age 30.7±5.6 years, and 30(33.3%) were in group 3 with mean age 29.1±5.5 years. Age, gestational age, body mass index and homeostatic model assessment for insulin resistance values were significantly higher in groups 2 and 3 compared to group 1 (p<0.05), while serum Tenascin-C values were not significantly different (p>0.05). Conclusion: HOMA-IR values and BMI were more reliable in diagnosing GDM before its onset, and should be included in the screening test for GDM in early pregnancy. Key Words: Diabetes, Gestational, Tenascin, Gynecology, Fasting, Enzyme, Immunosorbent, Diet